2020
DOI: 10.1097/md.0000000000022997
|View full text |Cite
|
Sign up to set email alerts
|

Full-endoscopic decompression for thoracic ossification of ligamentum flavum: surgical techniques and clinical outcomes

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In total, 23 relevant studies were included in this analysis, 10–32 enrolling 323 patients (177 males, 146 females) with a mean age of 58.40±10.06 years (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 23 relevant studies were included in this analysis, 10–32 enrolling 323 patients (177 males, 146 females) with a mean age of 58.40±10.06 years (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…With the evolution of endoscopic surgical tools, endoscopic techniques in spine surgery have gradually found utility in the treatment of TOLF. When compared with open surgeries, FESS procedures offer benefits in terms of minimal invasiveness and expedited recovery 9 11 . Nevertheless, FESS approaches have shown some new issues including limitations due to the coaxial approach in a single hole endoscope, a steep learning curve, and necessitating surgeons to possess extensive experience in endoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in minimally invasive spine techniques have shown the prospective application of full endoscopic spine surgeries (FESS) in treating TOLF 9 11 . However, these procedures are limited because of the steep learning curves in FESS, and controversies remain regarding approach selection, surgical instruments, and decompression strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Rutten et al reported a 20% (5/25) rate of complications including 1 dural tear, 1 epidural hematoma, 2 transient intercostal neuralgias, and 1 deterioration of myelopathy [ 28 ]. In our previous research on the endoscopic surgery for thoracic OLF, we found complications such as neck pain and dural tear [ 29 ]. However, no complication was observed in this study or in Choi and Guo's.…”
Section: Discussionmentioning
confidence: 99%